Identifying supervisory or managerial status in administrative records - Matthias Collischon (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2021)
Information on individuals holding a managerial or supervisory positions within establishments is important for various aspects of labor market research. However, identifying managers or supervisors in German administrative records is not straightforward. This paper uses survey information from the Panel Study Labour Market and Social Security (PASS) to predict managerial or supervisory tasks in administrative records that can be used to enhance the identification of managers and supervisors in the Sample of Integrated Labour Market Biographies (SIAB). Furthermore, I provide an applied example in which I calculate gender differences in the probability to hold a managerial position. – – Informationen darüber, ob Individuen eine Position mit Führungsaufgaben innehaben, sind wichtig für die Arbeitsmarktforschung. Leider ist es nicht einfach möglich, diese Aufgaben in deutschen administrativen Daten zu identifizieren. Dieser Beitrag nutzt Surveyinformationen aus dem Panel Arbeitsmarkt und soziale Sicherung (PASS), um Personen mit Führungsaufgaben in administrativen Daten, zum Beispiel dem SIAB, vorherzusagen. Als Beispiel für die Anwendung untersuche ich Geschlechterunterschiede in der Wahrscheinlichkeit, eine Position mit Führungsaufgaben zu haben.
Keywords: C53; J16; 330; Managers; SIAB; administrative data; supervisors; PASS